A classification of large wetlands in Africa's elevated drylands based on their formation, structure, and hydrological functioning using Earth Observation (EO) data and Geographic Information System (GIS) - Lidzhegu, Zwidofhelangani (Rhodes University, Faculty of Science, Institute for Water Research, 2020)
Due to wetland inaccessibility and limited wetland geomorphological studies, there is limited information on the geomorphological origin and hydrological functioning of different types of wetlands in Africa's elevated drylands. As a result, there is limited information for the development of a comprehensive wetland classification system that classifies wetlands based on long-term geomorphic processes that determine their formation and shape, their structure and hydrological functioning. Therefore, the current study was designed to classify large wetlands in Africa's elevated drylands based on processes that determine their formation, and shape their structure and hydrological functioning using remote sensing and Geographic Information System (GIS) techniques. Although wetlands perform a number of hydrological functions including groundwater recharge and water purification, the current study focuses mainly on their flood attenuation function. Detailed analysis of topographic information was undertaken using Shuttle Radar Topographic Mission (SRTM) elevations measured at the scale of 30 m x 30 m. LandsatLook and Google Earth images, tectonic as well as geological data were used as supplementary data for developing an understanding of the origin, structure and hydrological characteristics of wetlands. The Principal Component Analysis (PCA) of wetland environmental variables was used to identify and explain wetland heterogeneity. The results of the study showed that fluvial processes, tectonic history and the evolution of Africa's landscape played a fundamental role in the formation and evolution of wetlands. This study demonstrates a wide range of processes that contribute to wetland formation, structure and functioning. At one extreme it is clear that tectonic processes may be primarily responsible for the creation of basins that host wetlands. At another extreme, wetlands may be structured primarily by fluvial processes. At a third extreme are wetlands that superficially appear to be structured by fluvial processes, but which have their structures modified by gradual rising of the base level at their distal ends, either through marginal uplift adjacent to rift valleys, or through aggradation of a floodplain that blocks a tributary valley. Overall, the classification of wetlands considered in this study can be summarised into four distinct groupings, with two of these divided further into two groupings each: (1) Tectonic basins with little or no indication of fluvial development (Bahi and Wembere wetlands), (2) Tectonic basins evolving towards a wetland with a structure increasingly shaped by fluvial characteristics (Usangu wetland), (3) Fluvially modified valleys with a local base level at the toe of the wetland such as a resistant lithology or a tectonic control that limits the rate of incision of easily weathered and eroded lithologies, leading to valley widening and longitudinal slope reduction, which are of two distinct types: (a) With a catchment on Kalahari Group sediment that is transported fluvially as bedload, and therefore with no prominent alluvial ridge or backwater depressions (Upper Zambezi and Barotse wetlands), (b) With a catchment that produces abundant fine sediment that is deposited as overbank sediments, leading to channel migration via meandering and to the construction of an elevated alluvial ridge (Lufira wetland), (4) Fluvially modified basins with evidence of gradual elevation of the base level at the toe of the wetland, which are of two types: (a) Tectonic marginal rift valley uplift such that they behave more as depression wetlands rather than as wetlands shaped by fluvial processes (Kafue and Luapula wetlands), (b) Tributary valley wetlands blocked by aggradation of the trunk valley (Lukanga wetland). In conclusion, although few geomorphological studies have been conducted on southern African wetlands because of their inaccessibility, Africa's surface topography and its historical evolution, as well as aridity, provide an opportunity for illustrating the important role that the long-term tectonic, geological and geomorphological processes play in determining wetland origin, structure and dynamics. GIS methodology and Earth Observation (EO) data on the other hand, provide a practical means for acquiring information on inaccessible and hard to traverse wetland systems. A novel cut-and-fill approach for delineating wetlands from a Digital Elevation Model (DEM) was presented as another way in which GIS methodology and Earth Observation (EO) data can provide practical means for assessing inaccessible and hard to traverse wetland systems.
Keywords: Wetlands -- Africa -- Classification; Wetlands -- Africa -- Research; Wetlands -- Africa -- Monitoring; Topographical surveying -- Africa; Hydrological surveys -- Africa